2015
DOI: 10.14569/ijacsa.2015.061107
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Quality Prediction of Product Reviews

Abstract: Abstract-With the help of Web-2.0, the Internet offers a vast amount of reviews on many topics and in different domains. This has led to an explosive growth of product reviews and customer feedback, which presents the problem of how to handle the abundant volume of data. It is an expensive and time-consuming task to analyze this huge content of opinions. Therefore, the need for automated sentiment analysis systems is vital. However, these systems encounter many challenges; assessing the content quality of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Labbe et al (Labbé et al, 2015) conducted a study using computer generated literature with the aim of detecting fake articles. Almagrabi et al (Almagrabi & Malibari, 2015) carried out a survey related to product reviews and qualitative prediction of them. In order to identify sentiments in social media activities, Kumar and Sharma (Kumar & Sharma, 2017) analysed social media data.…”
Section: Spam Detection On Social Mediamentioning
confidence: 99%
“…Labbe et al (Labbé et al, 2015) conducted a study using computer generated literature with the aim of detecting fake articles. Almagrabi et al (Almagrabi & Malibari, 2015) carried out a survey related to product reviews and qualitative prediction of them. In order to identify sentiments in social media activities, Kumar and Sharma (Kumar & Sharma, 2017) analysed social media data.…”
Section: Spam Detection On Social Mediamentioning
confidence: 99%
“…Liu (2012), Pang and Lee (2008) and Vinodhini and Chandrasekaran (2012). Information about assessing the quality of product reviews can be found in Almagrabi, Malibari, and McNaught (2015).…”
Section: Related Workmentioning
confidence: 99%
“…Most works related to product clustering usually focus on analysis of customer behaviors [7] to cluster recommended products of interest [1] or analysis of product reviews [8]- [9] to study human opinions about the products features. These works usually use sentiment analyses or opinion mining [9]- [16] where human subjects are involved for assessment of the product features.…”
Section: Related Workmentioning
confidence: 99%
“…AP(f, C) denotes the average position of the feature f in vectors of cluster C, and is formulated in (8). This is used for the second criterion at (9).…”
Section: Vs ={ VI | I =1n } Represents Feature Vector Space Wherementioning
confidence: 99%